2021
DOI: 10.3390/md19010041
|View full text |Cite
|
Sign up to set email alerts
|

Topsentinol L Trisulfate, a Marine Natural Product That Targets Basal-like and Claudin-Low Breast Cancers

Abstract: Patients diagnosed with basal-like breast cancer suffer from poor prognosis and limited treatment options. There is an urgent need to identify new targets that can benefit patients with basal-like and claudin-low (BL-CL) breast cancers. We screened fractions from our Marine Invertebrate Compound Library (MICL) to identify compounds that specifically target BL-CL breast cancers. We identified a previously unreported trisulfated sterol, i.e., topsentinol L trisulfate (TLT), which exhibited increased efficacy aga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Within the CCLE drug screen, CHK1 inhibitors presented promising effects against basal cell lines. This result is supported by a recent study that showed CHK1 inhibitors being effective against basal-like breast cancer [43]. Interestingly, HDAC1/2 are known to sustain the phosphorylation and thus the activity of the checkpoint kinases CHK1/2, providing a link between these targets in BLCA [44].…”
Section: Discussionsupporting
confidence: 59%
“…Within the CCLE drug screen, CHK1 inhibitors presented promising effects against basal cell lines. This result is supported by a recent study that showed CHK1 inhibitors being effective against basal-like breast cancer [43]. Interestingly, HDAC1/2 are known to sustain the phosphorylation and thus the activity of the checkpoint kinases CHK1/2, providing a link between these targets in BLCA [44].…”
Section: Discussionsupporting
confidence: 59%
“…Topsentinol L trisulfate can inhibit the activation of AMP-activated protein kinase and checkpoint kinase 1 and promote activation of p38 in claudin-low breast cancer. Topsentinol L trisulfate has higher efficacy against claudin-low breast cancer than other types [ 281 ]. Most claudin-low breast tumors are reported to be ER – , PR – , and HER2 – ; therefore, the treatment of TNBC can play a guiding role in the treatment of claudin-low breast cancer to a certain extent [ 30 , 282 ].…”
Section: Breast Cancer Heterogeneity and Precise Treatmentmentioning
confidence: 99%